Pengembangan Komik Digital pada Pembelajaran IPAS Kelas IV Sekolah Dasar Negeri 35 Pontianak Selatan - Yurti, Yurti; Kresnadi, Hery; Salimi, Asmayani (AS-SABIQUN, 2023)
This study aims to develop digital comics for science lessons in grade IV Elementary Schools that are suitable for use to assist the learning process in the independent curriculum. This research is a development research adapted from the Borg & Gall research model which includes potential and problem steps, data collection, product design, product validation, design revision, product testing and product revision. Quantitative data in this study were obtained from the validation of media and material experts, student responses and teacher responses, while qualitative data from this study were obtained from suggestions and comments from media experts, material experts, students and teachers. Research instruments in the form of interview guidelines and questionnaires. The data analysis technique used in this study is the feasibility analysis of digital comics from the media and material aspects, as well as the responses from students and teachers. The results of the study show that the feasibility of digital comic media shows an average value of 4.95 with the criteria of "Very Eligible" and the eligibility of digital comic material shows a percentage of 4.26 with the criteria of "Very Feasible". Then the students' responses to digital comics on a small scale get an average score of 4.75 while the large-scale average score gets an average score of 4.82 with the criteria of "Very Good" and the teacher's response to digital comics gets an average score -an average of 5 with the criteria of "Very Good".